The spiritual vernacular of the Early Ottoman frontier - Grenier, Carlos, 19??- (Edinburgh)
x, 244 sayfa
Keywords: “The first book-length study in English on the Yazıcıoğlu brothers, among the most popular vernacular religious writers and thinkers of the early Ottoman period. Reconstructs the Yazıcıoğlus' biographies, assesses the heritage of their language and ideas and analyses the ways these were adapted to their distinct setting. Argues that Ottoman popular orthodoxy emerged as a synthesis of a cosmopolitan Islamic canon to address the needs of Turcophone Muslims of the Ottoman lands.Contributes to the study of non-elite intellectual life of Ottoman Muslims at the dawn of an imperial age. This study follows the lives and ideas of the Yazıcıoğlu brothers Mehmed Yazıcıoğlu and Ahmed Bican, Sufis of the frontier city of Gelibolu and authors of the most popular religious writings in Ottoman Turkish.Carlos Grenier places the Yazıcıoğlus' durable religious vision within their dynamic historical moment on the contested Ottoman borderlands. Examining how these non-elite writers deployed their own intellectual resources, he considers how they approached the religious sciences of the wider Islamic world. And he looks at how they created a religious synthesis appropriate for their own community, the growing Turcophone Muslim population of the Balkans and Anatolia.” --